Hepatic Encephalopathy: Early Diagnosis in Pediatric Patients With Cirrhosis - DARA*, Naghi; SAYYARI, Ali-Akbar; IMANZADEH, Farid (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Dara N, Sayyari AA, Imanzadeh F. Hepatic Encephalopathy: Early Diagnosis in Pediatric Patients With Cirrhosis. Iran J Child Neurol. 2014 Winter; 8(1):1-11. Objective As acute liver failure (ALF) and chronic liver disease (cirrhosis) continue to increase in prevalence, we will see more cases of hepatic encephalopathy. Primary care physician are often the first to suspect it, since they are familiar with the patient’s usual physical and mental status. This serious complication typically occurs in patients with severe comorbidities and needs multidisciplinary evaluation and care. Hepatic encephalopathy should be considered in any patient with acute liver failure and cirrhosis who presents with neuropsychiatric manifestations, decrease level of consciousness (coma), change of personality, intellectual and behavioral deterioration, speech and motor dysfunction. Every cirrhotic patient may be at risk; potential precipitating factors should be addressed in regular clinic visits. The encephalopathy of liver disease may be prominent, or can be present in subtle forms, such as decline of school performance, emotional outbursts, or depression. “Subtle form” of hepatic encephalopathy may not be obvious on clinical examination, but can be detected by neurophysiologic and neuropsychiatric testing. References: Ferenci P, Lockwood A, Mullen K, Tarter R, Weissenborn K, Blei AT. Hepatic encephalopathy definition, nomenclature, diagnosis, and quantification: final report of the working party at the 11th World Congresses of Gastroenterology, Vienna, 1998.Hepatology 2002;35:716-21. BleiAT,Cordoba J. Hepatic encephalopathy. AmJ Gastroenterol 2001;96:1968–76. Vaquero J,Chung C, Cahill ME, BleiAT. Pathogenesis of hepatic encephalopathy in acute liver failure. Semin Liver Dis 2003;23:259-69. Bajaj JS, Wade JB, Sanyal AJ. Spectrum of neurocognitive impairment in cirrhosis: Implications for the assessment of hepatic encephalopathy. Hepatology 2009; 50:2014–21. Norenberg MD, Jayakumar AR, Rama Rao KV, Panickar KS. New concepts in the mechanism of ammonia-induced astrocyte swelling. Metab Brain Dis 2007;22:219–34. Häussinger D, Görg B. Interaction of oxidative stress, astrocyte swelling and cerebral ammonia toxicity. Curr Opin Clin Nutr Metab Care 2010; 13:87–92. Hassall E, Benson L,HartM, et al.Hepatic encephalopathy after portacaval shunt in a noncirrhotic child. J Pediatr 1984;105:439–41. Zaki AE, Ede RJ, Davis M, Williams R. Experimental studies of blood brain barrier permeability in acute hepatic failure. Hepatology 1984;4:359–63. Zaki AE, Wardle EN, Canalese J, et al. Potential toxins of acute liver failure and their effects on blood–brain barrier permeability. Experientia 1983;39:988–91. Roy S, Pomier-Layrargues G, Butterworth RF, Huet PM. Hepatic encephalopathy in cirrhotic and portacaval shunted dogs: lack of changes in brain GABAuptake, brain GABAlevels, brain glutamic acid decarboxylase activity and brain postsynaptic GABA receptors. Hepatology 1988;8:845–9. Schliess F, Görg B, Häussinger D. RNA oxidation and zinc in hepatic encephalopathy and hyperammonemia. Metab Brain Dis 2009;24:119–34. Jalan R, Hayes PC. Hepatic encephalopathy and ascites. Lancet 1997;350:1309-15. Walker CO, Schenker S. Pathogenesis of hepatic encephalopathy–with special reference to the role of ammonia. Am J Clin Nutr 1970;23:619–32. Romero-Gómez M, Ramos-Guerrero R, Grande L, et al. Intestinal glutaminase activity is increased in liver cirrhosis and correlates with minimal hepatic encephalopathy. J Hepatol 2004; 41:49–54. Nance FC, Kaufman HJ, Kline DG. Role of urea in the hyperammonemia of germ-free Eck fistula dogs.Gastroenterology 1974;66:108–12. Llansola M, Rodrigo R, Monfort P, Montoliu C, Kosenko E, Cauli O, et al. NMDA receptors in hyperammonemia and hepatic encephalopathy. Metab Brain Dis 2007;22:321–35. Montoliu C, Piedrafita B, Serra MA, del Olmo JA, Urios A, Rodrigo JM, et al. IL-6 and IL-18 in blood may discriminate cirrhotic patients with and without minimal hepatic encephalopathy. J Clin Gastroenterol 2009;43:272–9. Desjardins P, Butterworth RF. The “peripheral-type” benzodiazepine (omega 3) receptor in hyperammonemic disorders. Neurochem Int 2002; 41:109–114. Häussinger D, Schliess F. Pathogenetic mechanisms of hepatic encephalopathy. Gut 2008;57:1156-65. McClain CJ, Zieve L, Doizaki WM, Gilberstadt S, Onstad GR. Blood methanethiol in alcoholic liver disease with and without hepatic encephalopathy. Gut 1980;21:318–23. Guevara M, Baccaro ME, Torre A, Gómez-Ansón B, Ríos J, Torres F, et al. Hyponatremia is a risk factor of hepatic encephalopathy in patients with cirrhosis: a prospective study with time-dependent analysis. Am J Gastroenterol 2009;104:1382–9. Poveda MJ, Bernabeu A, Concepción L, Roa E, de Madaria E, Zapater P, et al. Brain edema dynamics in patients with overt hepatic encephalopathy A magnetic resonance imaging study. Neuroimage 2010;52:481-7. Bernthal P, Hays A, Tarter RE, Van Thiel D, Lecky J, Hegedus A. Cerebral CT scan abnormalities in cholestatic and hepatocellular disease and their relationship to neuropsychologic test performance. Hepatology 1987;7:107-14. Sugimoto R, Iwasa M, Maeda M, Urawa N, Tanaka H, Fujita N, et al. Value of the apparent diffusion coefficient for quantification of low-grade hepatic encephalopathy. Am J Gastroenterol 2008;103:1413–20. Häussinger D. Low grade cerebral edema and the pathogenesis of hepatic encephalopathy in cirrhosis. Hepatology 2006;43:1187–90. Masson S, Mardini HA, Rose JD, Record CO. Hepatic encephalopathy after transjugular intrahepatic portosystemic shunt insertion: a decade of experience. QJM 2008;101:493–501. Boyer TD, Haskal ZJ. American Association for the Study of Liver Diseases. The role of transjugular intrahepatic portosystemic shunt (TIPS) in the management of portal hypertension: update 2009. Hepatology 2010;51:306. Kircheis G, Knoche A, Hilger N, Manhart F, Schnitzler A, Schulze H, et al. Hepatic encephalopathy and fitness to drive. Gastroenterology 2009; 137:1706–1715.e1–9. Bajaj JS, Saeian K, Schubert CM, Hafeezullah M, Franco J, Varma RR, et al. Minimal hepatic encephalopathy is associated with motor vehicle crashes: the reality beyond the driving test. Hepatology 2009;50:1175–83. Hartmann IJ, Groeneweg M, Quero JC, Beijeman SJ, de Man RA, Hop WC, et al. The prognostic significance of subclinical hepatic encephalopathy. AmJ Gastroenterol 2000;95:2029–2034. Bustamante J, Rimola A, Ventura PJ, Navasa M, Cirera I, Reggiardo V, et al. Prognostic significance of hepatic encephalopathy in patients with cirrhosis. J Hepatol 1999;30:890–895. Murray KF, Carithers RL Jr; AASLD. AASLD practice guidelines: evaluation of the patient for liver transplantation. Hepatology 2005;41:1407–32. Ferenci P, Lockwood A, Mullen K, Tarter R, Weissenborn K, Blei A. Hepatic encephalopathy– definition, nomenclature, diagnosis, and quantification: final report of theworking party at the 11thWorldCongresses of Gastroenterology, Vienna, 1998. Hepatology 2002;35:716–21. Kugler CF, Taghavy A, Fleig WE,Hahn EG. Visual P300 in acute hepatic encephalopathy resulting fromnon-A, non-B fulminant hepatitis: analysis of the course before and after orthotopic liver transplantation. Z Elektroenzephalogr Elektromyogr Verwandt 1991;22:259–63. Plauth M, Cabré E, Riggio O, Assis-Camilo M, Pirlich M, Kondrup J;DGEM (German Society for Nutritional Medicine); ESPEN (European Society for Parenteral and Enteral Nutrition). ESPEN guidelines on enteral nutrition: liver disease. Clin Nutr 2006;25:285–94. Gheorghe L, Iacob R, Vadan R, Iacob S, Gheorghe C. Improvement of hepatic encephalopathy using a modified high-calorie high-protein diet. Rom J Gastroenterol 2005;14:231–8. Elkington SG, Floch MH, Conn HO. Lactulose in the treatment of chronic portal-systemic encephalopathy. A doubleblind clinical trial. N Engl J Med 1969;281:408–12. 38. Conn HO, Leevy CM, Vlahcevic ZR, Rodgers JB, Maddrey WC, Seeff L, et al. Comparison of lactulose and neomycin in the treatment of chronic portalsystemic encephalopathy. A double blind controlled trial. Gastroenterology 1977;72(4 pt 1):573–83. Prasad S, Dhiman RK, Duseja A, Chawla YK, Sharma A, Agarwal R. Lactulose improves cognitive functions and health-related quality of life in patients with cirrhosis who have minimal hepatic encephalopathy. Hepatology 2007;45:549–59. Weber FL Jr. Effects of lactulose on nitrogen metabolism. Scand J Gastroenterol Suppl 1997;222:83–7. Morgan MY, Hawley KE. Lactitol vs. lactulose in the treatment of acute hepatic encephalopathy in cirrhotic patients: a doubleblind, randomized trial. Hepatology 1987;7:1278–84. Dawson AM, McLaren J, Sherlock S.Neomycin in the treatment of hepatic coma. Lancet 1957;273:1262–8.248. Atterbury CE, Maddrey WC, Conn HO. Neomycinsorbitol and lactulose in the treatment of acute portal systemic encephalopathy. A controlled, double-blind clinical trial. Am J Dig Dis 1978;23:398–406. 44. Berk DP, Chalmers T. Deafness complicating antibiotic therapy of hepatic encephalopathy. Ann Intern Med 1970;73:393–6. Cabrera J, Arroyo V, Ballesta AM, Rimola A, Gual J, Elena M, et al. Aminoglycoside nephrotoxicityin cirrhosis. Value of urinary beta 2-microglobulin to discriminate functional renal failure from acute tubular damage. Gastroenterology 1982;82:97–105. Blei AT, Córdoba J; Practice Parameters Committee of the American College of Gastroenterology. Hepatic encephalopathy. Am J Gastroenterol 2001;96:1968–76. Rothenberg ME, Keeffe EB. Antibiotics in the management of hepatic encephalopathy: an evidence based review. Rev Gastroenterol Disord 2005;5(suppl 3):26–35. Murphy N, Auzinger G, Bernel W, Wendon J. The effect of hypertonic sodium chloride on intracranial pressure in patients with acute liver failure. Hepatology 2004;39:464-70. 49. Charlton M. Branched-chain amino acid enriched supplements as therapy for liver disease. J Nutr 2006;136(suppl 1):295S–298S. Egberts EH, Schomerus H, Hamster W, Jürgens P. [Branched-chain amino acids in the treatment of latent porto-systemic encephalopathy. A placebo-controlled double-blind cross-over study] [in German]. Z Ernahrung swiss 1986; 25:9–28. Plauth M, Egberts EH, Hamster W, Török M, Müller PH, Brand O, et al. Long-term treatment of latent portosystemic encephalopathy with branched-chain amino acids. A double-blind placebo-controlled crossover study. J Hepatol 1993;17:308–14. Les I, Doval E, García-Martínez R, Planas M, Cárdenas G, Gómez P, et al. Effects of branched-chain amino acids supplementation in patients with cirrhosis and a previous episode of hepatic encephalopathy: a randomized study. Am J Gastroenterol 2011;106:1081-8. Schliess F, Görg B, Häussinger D. RNA oxidation and zinc in hepatic encephalopathy and hyperammonemia. Metab Brain Dis 2009;24:119–34. Efrati C, Masini A, Merli M, Valeriano V, Riggio O. Effect of sodium benzoate on blood ammonia response to oral glutamine challenge in cirrhotic patients: a note of caution. Am J Gastroenterol 2000;95:3574–8. Schmid M, Peck-Radosavljevic M, König F, Mittermaier C, Gangl A, Ferenci P. A double-blind, randomized, placebo-controlled trial of intravenous L-ornithine-Laspartate on postural control in patients with cirrhosis. Liver Int 2010;30:574–82. Blei AT. MARS and treatment of hepatic encephalopathy [in Spanish). Gastroenterol Hepatol 2005;28:100-4. Heemann U, Treichel U, Loock J, Philipp T, Gerken G, Malago M, et al. Albumin dialysis in cirrhosis with superimposed acute liver injury: a prospective, controlled study. Hepatology 2002;36:949–58. Zidi SH, Zanditenas D, Gelu-Siméon M, Rangheard AS, Valla DC, et al. Treatment of chronic portosystemic encephalopathy in cirrhotic patients by embolization of portosystemic shunts. Liver Int 2007;27:1389-93. Dhar R, Young GB, Marotta P. Perioperative neurological complications after liver transplantation are best predicted by pre-transplant hepatic encephalopathy. Neurocrit Care 2008;8:253–8. Teperman LW, Peyregne VP. Considerations on the impact of hepatic encephalopathy treatments in the pretransplant setting. Transplantation 2010; 89:771–8. 61. Senzolo M, Pizzolato G, Ferronato C, Chierichetti F, Boccagni P, Dam M, et al. Long-term evaluation of cognitive function and cerebral metabolism in liver transplanted patients. Transplant Proc 2009; 41:1295–1296. Butterworth RF. Neuronal cell death in hepatic encephalo- pathy. Metab Brain Dis 2007;22:309–320. DiMartini A, Chopra K. The importance of hepatic encephalo -pathy:pre-transplant and post-transplant. Liver Transpl 2009;15:121–3. Saner FH, Nadalin S, Radtke A, Sotiropoulos GC, Kaiser GM, Paul A. Liver transplantation and neurological side effects. Metab Brain Dis 2009;24:183-7. Sotil EU, Gottstein J, Ayala E, Randolph C, Blei AT. Impact of preoperative overt hepatic encephalopathy on neurocognitive function after liver transplantation. Liver Transpl 2009;15:184-92.